An adaptive comparison-based internal sorting algorithm (S-sort) - Seño, Jose L. (Animo Repository, 2003)
Ssort, an adaptive comparison-based internal sorting algorithm in the same order O(n log n) comparisons as that of Classical Quicksort, has been developed. The best case and worst case time complexities of the proposed sorting algorithm have also been analyzed. It was also empirically evaluated on randomly-generated data sets with various sortedness ratios. With the application of adaptability measurement, Adaptive Ssort has improved the performance of Ssort. Its best case time complexity is O(n) comparisons while its worst case is O(n log n) comparisons. Similarly, its performance was evaluated and compared with classical Quicksort.